He'm ¢i¢imat, 'La Chichimeca' - Gutiérrez Morales, Salomé; Wichmann, Søren (Tlalocan, 2013)
The paper presents a transcription and Spanish translation of a folktale in Sierra Popoluca, a Mixe- Zoquean language spoken in Southern Veracruz, in the municipio of Soteapan. Published texts in this language are very scarce, so the text may serve as a resource for future studies. The text was dictated to Salomé Gutiérrez Morales, a trained linguist as well as native speaker, by his close relative Jesús Gutiérrez from the village of Amamaloya. It was subsequently checked for details in transcription and translation by both authors in collaboration with another member of the speech community, Nicasio Gutiérrez Juárez. Opting not to present a morphological analysis, the authors have chosen a very literal translation style which should make it simpler, with some help from a grammar such as Elson (1960), to work out an analysis. As is true of much of the lore of the Popolucas, the contents of the tale is predominately of European extraction, in part rather closely resembling the story of "Hansel and Gretel" from the collection of the German brothers Grimm, and similar stories known also from the oral traditions of Spain, among other European countries. It appears to be rather popular in most parts of southern Veracruz, and perhaps beyond, not only among other indigenous groups, such the Popolucas of Texistepec, but also in the general, rural Spanish-speaking population. The story may be summarized as follows. Two children, a boy and a girl, are left out in the country by their father because they are unwanted by their stepmother. They are adopted by an old, blind, wicked woman, the Tzitzimat (or Chichimeca, in Nahuatl-derived Spanish). However, managing to kill the Tzitzimat, the children make their escape. From the cauldron into which they have pushed her spring two dogs. When, later on, the girl h as plans to marry a giant whom they have met during their wanderings, the dogs help out the boy. After an unsuccessful attempt by the dogs to kill the giant, the girl takes revenge on them by hiding a bone in her brother's pillow to kill him. The boy is brought back to life by the dogs. Later follows an episode where the boy saves the life of a princess, killing a snake which had been a threat to her. A Negro, who falsely claims the honor of having saved the life of the princess, is shown to be a liar when the dogs bring the tongue of the serpent to the king as proof that the boy was the true savior of the king's daughter.